2019
DOI: 10.3390/f10060488
|View full text |Cite
|
Sign up to set email alerts
|

Plant Pathogenic Fungi Associated with Coraebus florentinus (Coleoptera: Buprestidae) Attacks in Declining Oak Forests

Abstract: The black-banded oak borer, Coraebus florentinus, is an emerging pest of oak trees in the western Mediterranean region. Larvae of the insect are xylophagous and progressively excavate an annular gallery that interrupts sap flow, resulting in the death of the attacked branches. Until now, limited information has been available regarding the ecological interactions between C. florentinus and the main plant pathogenic fungi involved in the etiology of oak decline. Knowledge of these interactions is important in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 64 publications
(53 reference statements)
0
18
0
Order By: Relevance
“…Here, we used inoculation experiments to test the pathogenicity of two Cryphonectria species closely related to one of the most lethal invasive forest pathogens, namely Cryphonectria parasitica. One species (C. japonica) is still not present in Europe, whereas the other (C. naterciae) seems to be currently restricted to Portugal and some areas in Italy (Bragança et al, 2011;Pinna et al, 2019). Inoculation experiments have previously been used to identify potential new host species of other invasive plant pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we used inoculation experiments to test the pathogenicity of two Cryphonectria species closely related to one of the most lethal invasive forest pathogens, namely Cryphonectria parasitica. One species (C. japonica) is still not present in Europe, whereas the other (C. naterciae) seems to be currently restricted to Portugal and some areas in Italy (Bragança et al, 2011;Pinna et al, 2019). Inoculation experiments have previously been used to identify potential new host species of other invasive plant pathogens.…”
Section: Discussionmentioning
confidence: 99%
“… Cryphonectria decipiens [ 44 ]) was isolated from Castanea sativa and Quercus spp. in Portugal, Sardinia, and Algeria ( 45 47 ). Inoculation experiments showed that both C. japonica and C. naterciae are significantly less virulent on Ca.…”
Section: Introductionmentioning
confidence: 99%
“…sativa and Quercus spp. in Portugal, Sardinia and Algeria (Bragança et al, 2011;Pinna et al, 2019;Smahi et al, 2018). Inoculation experiments showed that both C. japonica and C. naterciae are significantly less virulent on Ca.…”
Section: Introductionmentioning
confidence: 99%